Notions of probability of children with disabilities of the first grade of special education (Edma 0-6: Educación Matemática en la Infancia, 2021)
In Mexico, the probability is increasingly absent in regular primary education and does not occur in special education. So the document is interested in pointing out the first notions of probability of children with disabilities in the first grade (5 and 6 years) of special education and its relationship with the compensatory schemes that favor their probabilistic thinking. The research, qualitative and denominated in progress, is in line with the proposal of Three Main Axes: epistemological, cognitive and social. The procedure followed the guidelines of the operating body and the teaching analysis unit. Under the method of experience, teaching strategies and control sheets were implemented; The data recording techniques used were video recording, transcription and writing on paper. The results concern notions of sample space and random variable; as well as the identification of first uses of compensatory schemes for those mathematical concepts.
Keywords: Probability; Special Education; Disability; School mathematics